Antistaphylococcal and antibiofilm activities of ethanolic extract of Piper cubeba L. - Velu, Selvi (2018)
Staphylococcus aureus is a very adaptable foodborne pathogen responsible for food outbreaks and a source of cross contamination in fresh and processed foods worldwide. Methicillin-resistant S. aureus (MRSA) strains which were initially addressed in humans is being marked as emerging community acquired pathogen in recent years. The resistance of staphylococci towards various novel and existing antimicrobial agents has developed as a problem. Noticeably, the significance of medicinal plants and traditional health practices has gained increasing attentions principally in solving the impact of emergence, spread and resistance of microorganisms of the world. Simultaneously, there is a concern in the field of food safety, quality and preservation to counter the rising of resistant pathogens and the limitation of synthetic chemical additives in the food system. Among the plants investigated to date, one showing enormous potential is the pepper family otherwise known as Piperaceae. Piper cubeba L. has infinite medicinal properties and practiced to treat a number of diseases. In this study, the Piper cubeba L. extract was examined for its antistaphylococcal and antibiofilm activity against Staphylococcus aureus food isolates, S. aureus human isolates and a reference strain S. aureus ATCC6538P. P. cubeba L. berries were extracted using ethanol, methanol and water as solvent. The antimicrobial activity of ethanol, methanol and water extracts of P. cubeba L. against S. aureus isolates in terms of disc diffusion was performed. Further, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and time kill curve were performed using ethanol extract referring to standard method of Clinical and Laboratory Standards Institute (CLSI). The ethanolic P. cubeba L. extract was assessed for its stability at various temperature and pH conditions relevant to food production and storage. Scanning electron microscopy (SEM) was used to visualize the effect of ethanolic P. cubeba L. extract on representative S. aureus. The bioactive compounds present in ethanolic P. cubeba L. extract were determined using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography-Mass Spectrometry (LC-MS). Biofilm forming patterns of S. aureus isolates and antibiofilm activity of ethanolic P. cubeba L. extract were performed in presterilized flat-bottom 96-well microplate and were quantified using 2,3-bis (2-methoxy-4-nitro-5-sulfophenyl)-5-[(phenyl-amino) carbonyl]-2H tetrazolium-hydroxide (XTT) reduction assay. The effect of ethanolic P. cubeba L. extract was assessed on cut-up parts of chicken (breast, wing and drumstick) as natural sanitizer. Visual attribute sensory acceptability was evaluated on raw and steamed chicken meat treated with ethanolic P. cubeba L. extract. Toxicity effect of the extract was evaluated using the brine shrimp lethality assay. The results showed that ethanol and methanol P. cubeba L. extract exhibited significant diameter of inhibition zone in the range of 7.23 – 8.50 mm and 7.13 – 8.57 mm respectively, against S. aureus isolates. MIC and MBC of ethanolic extract were in the range of 0.625 – 2.5 mg/ml and 1.25 – 5 mg/ml against all tested isolates, respectively. The time-kill curve plots revealed S. aureus food isolates CM10 and CM14 were killed within 1 h of incubation at a concentration of 4× MIC. As for S. aureus human isolate and ATCC6538P the time-kill curve plot revealed bacteriostatic effect of the P. cubeba L. extract. Trends of increasing, decreasing and constant MIC and MBC values were observed upon heat treated ethanolic P. cubeba L. extract as compared to non-heat treated extract. Generally, the pH altered extracts varied the MIC and MBC values of the S. aureus isolates. Under SEM observation, the treated cells underwent a significant transition from initially smooth surfaces cells to completely distort and shrank cells. The major volatile bioactive compounds determined using GC-MS were β-cubebene, cubebol, α-copaene, α-cubebene, caryophyllene and germacrene-D. Non- volatile compounds identified by LC-MS were 5,7-dihydroxy- 3',4'-dimethoxy-6,8-dimethylflavone, brosimacutin B, phellodensin D, 9E,12Z,15Zoctadecatrienoic acid, 2,4-dimethyl-tetradecanoic acid, eriodictyol 7,3'-dimethyl ether 4'-prenyl ether, erioflorin methacrylate, 12-oxo-5E,8E,10Z-dodecatrienoic acid and (S)-β-himachalene. S. aureus isolates exhibited strong adherent ability at 37°C and 28°C while weak and non-adherent capability mostly observed at 7°C. The biofilm formation of S. aurues can be inhibited by sessile minimal inhibitory concentration (SMIC) of 6.25 – 25 mg/ml and the formed S. aurues biofilm can be eradicated by minimal biofilm eradication concentration (MBEC) values of 25 – 50 mg/ml. In general, reduction 3 Log10 of S. aureus, total plate count, E. coli and coliform was started to observe at ethanolic P. cubeba L. extract of 0.50% on the cutup parts of chicken. P. cubeba L. sanitized raw and steamed chicken meat at 0.05%, 0.50% and 5.00% was accepted by the panelists. Brine shrimp lethality test exhibited no significant toxicity (LC50 = 6.98 mg/ml) against brine shrimp naupili. In conclusion, ethanolic P. cubeba L. extract with potential antimicrobial and antibiofilm activities could be prominently marked as a valuable natural antimicrobial, antibiofilm, and sanitizing agent in the food safety field.